TRANSFORMATIONAL LEADERSHIP OF VILLAGE HEAD IN IMPROVING PUBLIC SERVICE INNOVATION IN TAPENPAH VILLAGE, INSANE DISTRICT, NORTH CENTRAL TIMOR REGENCY - Stefanus Bekun; Yohanes Fina (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Creative service requires a transformational leader to improve public service innovation in the village. Public services in Tapenpah Village, Insana District, North Central Timor Regency (TTU) cover various aspects such as health, administration, and social assistance. Services at the village office are also required to provide excellent service. TAJUK (Tapenpah Just Click) innovation is an excellent service system for the community to make it easier for people to obtain various letters without having to come to the village office. The research method used in this study is a qualitative method with the focus of the research, namely: Showing ideal influence, generating inspirational motivation, providing intellectual stimulation, enforcing followers by paying attention to followers. The results of the study indicate that the Tapenpah Village government realizes public service innovation in the village by influencing the community to carry out services online, providing motivation and intellectual stimulus to the community to learn to access the village website, and providing good attention to the community. This innovative service can be influenced by the transformational leadership of the village head in improving public service innovation in Tapenpah Village, Insana District, TTU Regency.